Analisis Menilai Keadaan Financial Perusahaan Dengan Metode Common Size Pada PT. Mayora Indah Tbk Dan Perusahaan Kompetitor Periode 2015-2021 - Ganis Anggraeni Aidhul Fitri; Taufik Akbar; Aprilia Dian Eva Sari (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
Financial performance is a form of achievement on the results of management's work to achieve the company's goals in conducting an assessment by measuring financial ratios periodically the company's operational activities according to the criteria approved by the company. This study uses common size analysis which is a financial statement calculation technique to be simpler generally in the form of horizontal and vertical analysis, so as to show the relationship and trend of the company's financial position. This study aims to determine the circumstances, conditions and financial proportions in more detail of the company under study. The study was conducted descriptively with a comparative approach by processing secondary data in the form of company financial statements. The object of research is a food and beverage company listed on the IDX, namely PT. Mayora Indah Tbk and its competitor, PT. Indofood CBP Sukses Makmur Tbk and PT. Siantar Top Tbk. Sampling was taken with a research period of 7 years, from 2015 to 2021 and found as many as 21 financial data. The method used is Common size analysis. The results obtained are financial management in terms of liquidity is mostly done by PT. Indofood CBP Sukses Makmur which is offset by assets that also increase is reflected in the management balance sheet report showing optimal management with stable sales over time, PT. Mayora Indah Tbk transfers a lot of funds to the company's assets and equity, but in a pandemic situation, management still has difficulty managing funds so that operating profit has decreased, while PT. Siantar Top Tbk shows a unique pattern of liabilities with debt rising and falling from year to year based on profit appears very sharp decline in addition the company has a proportion of funds that mostly go to sales expenses compared to other account components.